RETROFITTING OF SELF COMPACTING RC HALF JOINTS WITH INTERNAL DEFICIENCIES BY CFRP FABRICS (Jurnal Teknologi (Sciences & Engineering), 2020)
An experimental study has been conducted to scrutinize the response of reinforced self-compacting concrete half joints upgraded with CFRP strips. Fourteen RC half joints have been tested. Two values of shear slenderness ratio were considered, namely 1.5 and 1.0. Two beams have been treated as reference specimens (with the design steel), and the twelve other beams were casted with deficiency in steel of the hanger and the extended end regions relative to the control beams. Eight of these beams have been strengthened with different arrangements to discuss the influence of shear slenderness ratio and strengthening arrangement on the overall performance of such joint elements. It is found that the reduction in nib-main steel by about 50% results in decreasing load capacity by about 36% and 15% for shear slenderness ratio of 1.5 and 1.0 respectively. Also, it is found that the orthogonal arrangement combined with inclined strips yielded the best results in terms of preventing the diagonal shear failure at the re-entrant corner with maximum enhancement in load capacity by 18%. In addition, the maximum improvement in failure load when strengthening hanger region by such alignment was about 23%. Results also revealed that the effective stiffness and ductility ratio enhanced with reducing shear span of a half joint and may be adopted as a good indicator to evaluate the suitable strengthening scheme. Moreover, it is concluded that the relative displacement method for predicting the ductility ratio is more applicable than that based on the dissipated energy.